Molecular cell Biology - LODISH, Harvey; MATSUDAIRA, Paul; BERK, Arnold; ZIPURSKY, Lawrence; BALTIMORE, David; DARNELL, James (W.H.FREEMAN AND COMPANY AND SUMANAS MULTIMEDIA DEVELOPMENT SERVICES, 2000)
1 disco (CD) ; 12 cm.